Stimulated-Emission-Pumping Laser-Induced-Fluorescence Spectroscopy of Phenol and Anisole. Issue 1 (1994) - Takayanagi, Masao; Hanazaki, Ichiro
Abstract : The SEP–LIF (stimulated emission pumping-laser induced fluorescence) technique was applied to the investigation of dynamical behavior of vibrationally excited phenol and anisole produced in the supersonic expansion. In the SEP–LIF scheme, a molecule excited to a specific vibrational state by SEP is detected by measuring the LIF excitation spectrum with an appropriate delay to probe the vibrational relaxation. Four vibrational states, 6a1, 16a2, 121 and 11, of phenol, and six vibrational states, 18b1, 18b2, 6a1, 121, 16a2 and 11, of anisole were investigated. For both of phenol and anisole, it is found that the relaxation of the vibrational states below 1, 000 cm -1 in the ground electronic state is so slow under the collisionless condition that only the transitions from the vibrational states initially prepared by SEP are observed as the SEP-induced bands in the SEP–LIF spectra. The low frequency torsional motion of methyl group in anisole does not accelerate IVR (intramolecular vibrational redistribution) much in this energy region.